Religious Pop: Zakir Naik and the Ideological Contestation - Livo Februsa (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2023)
Zakir Naik is a digital preacher. He is famous, along with the popularity of social media platforms that facilitate da'wah recordings and controversial events, including religious communications. Zakir Naik's communication became controversial because the material related to comparing religions, especially Islam and Christianity. This article focuses on the controversial discourse of Zakir Naik's da'wah by exploring the textual corpus of artifacts of audiovisual recordings on social media, especially Youtube, online media reports, and public comments represented by netizens on Youtube accounts regarding Zakir Naik. The findings show ideological contestation in media, public, and account framing, which is reflected in the various issues and views surrounding Zakir Naik's da'wah. This study is the first to dissect ideologies related to digital da'wah discourse, especially in Indonesia, a country with the world's largest and most plural Muslim population.